Welcome to Silver Street Farm - Davies, Nicola 1958- (Walker, 2011)
Three children, two poodles and a lime flavoured jelly baby - what more do you need to open a city farm? A friendly policeman, some singing supporters and a dog that herds chickens, of course!
Keywords: Silver Street Farm (Imaginary place) / Juvenile fiction; Farm life / Juvenile fiction; Children's stories